1998
DOI: 10.1177/154193129804202387
|View full text |Cite
|
Sign up to set email alerts
|

Requirements Analysis for a Night Vision Device Driver Training Aid

Abstract: The use of night vision devices (NVDs), including image intensification (12) and infrared (IR) devices, has resulted in enhanced operations, increased mobility, and potentially safer operations by military drivers, but also has resulted in a higher exposure to the hazards of the night environment. Evidence suggests that many of the problems drivers are experiencing at night when driving with I2 devices are due to perceptual errors. Furthermore, skills using I2 devices are highly perishable but improve with fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Dyer and Young (1998) provided a comprehensive review of the uses of NVGs for ground forces. Uses include aiming and shooting with the aid of NVGs (e.g., Angel, 2005; Dyer, Smith, & McClure, 1995), driving vehicles (e.g., Ruffner, Piccione, & Woodward, 1998; Tsimhoni & Green, 2002), dismounted infantry terrain traversal (e.g., Angel, 2004), and medical operations in combat conditions (Schwartz, 2001).…”
Section: The Context and The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyer and Young (1998) provided a comprehensive review of the uses of NVGs for ground forces. Uses include aiming and shooting with the aid of NVGs (e.g., Angel, 2005; Dyer, Smith, & McClure, 1995), driving vehicles (e.g., Ruffner, Piccione, & Woodward, 1998; Tsimhoni & Green, 2002), dismounted infantry terrain traversal (e.g., Angel, 2004), and medical operations in combat conditions (Schwartz, 2001).…”
Section: The Context and The Environmentmentioning
confidence: 99%
“…In addition, training is required for perceptual and cognitive skills in various tasks. Ruffner et al (1998) reported that the training of perceptual skills required when driving with NVGs included detecting and determining the depth of depressions and ditches, judging vehicle distance and closure rates, detecting and estimating the distance to obstacles and roadway edges, and recovering from exposure to bright light sources. Reising and Martin (1995) and Niall et al (1999) focused on training a very specific and critical perceptual skill of distance estimation.…”
Section: The Practical Implicationsmentioning
confidence: 99%